การศึกษาเนื้อหาการสอบเปียโนระดับประกาศนียบัตรชั้นสูงด้านการแสดง ของสถาบันรอยัล ลอนดอน สหราชอาณาจักร - อักษรศิริ, เสาวลักษณ์; สุทธจิตต์, ณรุทธ์ (An Online Journal of Education, 2018)
The objectives of this research were to study the contents of piano examinations and present guidelines for the preparation of diploma level music performances of The Associated Board of the Royal Schools of Music (ABRSM : DipABRSM) in the UK. The researcher used the qualitative research method focused on content analysis and interview, and descriptive data analysis which collected data in the same topics from different sources. Key informants were determined by purposive sampling method, who divided into two groups: 1) five professors who are experts in teaching piano; and 2) two exam takers applicants who have experience with piano examinations in the diploma level. The results of the research found that diploma level piano examinations have four sessions which are Recital, Viva Voce, Program Note and Quick Study. To prepare for the examination, the applicants had to not only thoroughly understand the examination contents but also use analytical thinking skills for choosing an appropriate performance program. Collecting performance data about each song as reference for Viva Voce and Program Note. It was also necessary for the applicant to have the appropriate resources and preparation activities was important, such as books and exercises for the Quick Study session and minor performance activities that act as mock-up performances that create an atmosphere of the actual examination ahead of time, to ensure completeness and confidence to achieve effective results in the piano examination.